East 43rd Street. - Battersby, Alan (New York Cambridge University Press, 2000)
New York on a cold, wet evening,six days before Christmas. Nathan Marley, an old-fashioned private investigator in a modern world,is relaxing in McFassens Bar. A very expensive-looking woman walks in and out of the bar and Marley follows her. Thats mistake and Chrastmas is about to become a lot more exciting for Marley than he expected.
Keywords: Reading